Look out! at home - Llewellyn, Claire; Gordon, Mike (Wayland London, 2007)
Covers basic issues of safety around a typical home. This book looks at electrical safety, safety with hot and sharp items, fire, avoiding falls, household cleaners and medicines. It addresses the child reader and helps to foster a sense of responsibility for their own safety in the home.